In vitro collecting techniques for germplasm conservation - Pence, V.C.; Sandoval, J.A.; Villalobos A., V.M.; Engelmann, F.; International Plant Genetic Resources Institute (2002)
During the early 1980s, while searching for ways to more fully utilize the techniques of plant biotechnology, IPGRI (the International Plant Genetic Resources Institute, then the International Board of Plant Genetic Resources, IBPGR) suggested that germplasm be collected by means of in vitro methods. Between 1990 and today, research in this area has been performed by different groups, leading to the development and/or optimization of in vitro collecting techniques for various additional species including coconut, taro, tropical rainforest tree species and wild and endangered species. This technical bulletin comprises three separate parts. The first part (theoretical background to in vitro collecting), consists of three chapters regarding the rationale behind the development of in vitro collecting and its potential for the conservation of crops and wild or endangered species and the control of contamination, a critically important step which conditions the successful development of any in vitro collecting protocol. The second part (case studies) comprises nine chapters, each describing the work performed for the development of in vitro protocols for a particular species or group of species. The protocols described can be applied directly for collecting germplasm of any of the species concerned. However, circumstances will differ from one collecting mission to the next and it can be expected that these protocols will have to be adapted to these circumstances. Therefore, the aim of these chapters is to illustrate the range of protocols, from the simplest to the most sophisticated, which can be developed for in vitro collecting germplasm of a given species and to highlight the critical steps of such protocols. Such information should be used by the readers as a guide for the development of protocols for the species of their own interest. The last part (prospects) consists of a single chapter which analyses the future of in vitro collecting for improving the conservation and use of plant genetic resources. This technical bulletin includes references up to 2001. It includes both theoretical and practical aspects, aims to provide a resource for those wishing to understand the basic concepts of adapting plant tissue culture methods to field collecting.